A feasibility study on home-based kyphosis-specific exercises on reducing thoracic hyperkyphosis in older adults - Wei Ying Li; Jinling Lu; Yong Dai; Agnes Tiwari; Pui Hing Chau (Elsevier, 2023)
Objectives: This study aimed to assess the feasibility of the home-based kyphosis-specific exercises among Chinese older adults with different exercise habits and explore its potential effects on reducing the kyphosis angle and improving physical performance. Methods: A single-group, pre-and post-test design was conducted according to CONSORT 2010 statement: extension for pilot and feasibility trials. A total of 20 participants aged ≥60 with thoracic hyperkyphosis and rehabilitation potential were recruited from four local communities in Wuhan, China. Participants underwent a six-week home-based kyphosis-specific exercises intervention that included warm-up, muscle strengthens, spinal alignment, spinal mobility and flexibility, and cool down five sections (22 exercises). The intervention involved seven 1-h group classes and 35 times daily home practice with identical content. At pre- and post-intervention, the participants' kyphosis angle in two standing postures, static balance, dynamic balance, cardiopulmonary function, dynamic gait assessment, pain, and self-image were assessed and compared. Feasibility was assessed by group class attendance, home practice adherence, and participant evaluations. Results: All participants completed group classes and >75% home practice. Post-intervention, the participant's kyphosis angle in relaxed and best-standing postures was changed by −12.0° (−15.5°, −4.0°) (Z = − 3.98, P < 0.001）and −10.0° (−14.0°, −5.3°) (Z = −3.79, P < 0.001), respectively. In addition, participants had significantly less pain (P < 0.001), better self-image (P < 0.001), and improved performance in five physical assessments (P < 0.01). Different pre-intervention hyperkyphosis angle and daily physical activity did not affect intervention effects. Most participants considered the interventional exercise as moderate intensity and satisfactory. Conclusions: Home-based kyphosis-specific exercises showed the possibility of being a feasible intervention. And it was advantageous to reducing the kyphosis angle and improving physical performance.